Bioassay-guided isolation of antibiotics from selected marine bacteria - Choo, Jenny Cheng Yi. (Universiti Malaysia Sarawak (UNIMAS), 2011)
As a response to the widespread emergence of antibiotic resistant bacteria, a study was devised to isolate selected marine bacteria to test for its antibacterial activity. A total of six bacterial isolates which were P5.1.2, 3.1.2, B2.4A, B.24C, B2.6A, and S 1.2.3 were subjected to preliminary screening via agar-well diffusion assay against Gram-positive (Staphylococcus aureus) and Gram negative (Escherichia coli, Enterobacter aerogenes, and Salmonella typhi) test bacteria. Bacterial isolate P5.1.2 which was tentatively identified as Klebsiella sp. was only found active against Gram positive test bacteria while others showed no activity. Antibiotic extraction from this isolate P5.1.2 was done from culture growing it on solid media. Dried cultures were then subjected to subsequent extraction using six solvents which were hexane, chloroform, dichloromethane, ethyl acetate, methanol, and water. A time-course experiment was conducted to determine the optimum age of harvesting. All six extracts from the selected bacterial isolate were subjected to antibacterial screening against the test bacteria via agar-well diffusion method and the presence of halo around the wells was examined. Methanol, chloroform, and ethyl acetate crude extracts showed antibacterial activities and the minimum inhibitory concentration (M1C) values were I mg/ml, 0.25 mglml and 0.125 mg/ml respectively. These results supports that marine environment is capable of producing new antibiotic substances.